Rävelden : Dola Suite - Ömalm, Torbjörn (Luleå tekniska universitet, Musik och dans, 2016)
The album Dola Suite (Rävelden) was released in May of 2016 through the Italian label Setola Di Maiale. Luigi Bozzolan - piano Torbjörn Ömalm - electric guitar Markus Larsson - drums/percussion Feat. Achille Succi - alto sax and bass clarinet Engineered, recorded and mixed by Johan Karlsson at Twin City Choir Studios, October 2015 in Malmberget – Sweden. Mastered by Ronald Vikström in February 2016. All songs written/improvised by Rävelden. The trio is based in Gällivare, Swedish Lapland, and plays music that is based on a collective improvisation following its own identity. Achille Succi contributed with some really superb musicianship to the trio in a vibrant arctic studiosession. A "Dola" is an explosive that has failed to detonate for some reason and we tried to improvise out of that idea in this three part suite.